1993
DOI: 10.1111/j.1471-6402.1993.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Menopause

Abstract: Menopause is a complex biopsychosocial phenomenon that is influenced by women's attitudes, the attitudes of their partners, families, and friends, and societal norms.Previous research has shown that attitudes can be influenced by many factors, such as age and menopausal status. This study examined men's and women's attitudes toward several facets of menopause, including fertility, attractiveness, personal growth, emotional stability, and sexuality, using an Amazon Mechanical Turk sample of 194 females and 151 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 21 publications
2
1
0
2
Order By: Relevance
“…A previous study reported that both postmenopausal women and their healthcare providers believed that attitudes toward menopause can have an important role in the formation of women's experience about menopause. 5 The same finding was also reported by additional prospective studies. 6 Jurgenson et al 7 found a strong relationship between negative attitudes toward menopause and aging, increased severity, and the onset of menopausal symptoms.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…A previous study reported that both postmenopausal women and their healthcare providers believed that attitudes toward menopause can have an important role in the formation of women's experience about menopause. 5 The same finding was also reported by additional prospective studies. 6 Jurgenson et al 7 found a strong relationship between negative attitudes toward menopause and aging, increased severity, and the onset of menopausal symptoms.…”
supporting
confidence: 81%
“…Similarly, attitudes toward menopause may affect the severity of menopausal signs and symptoms and affect women's experience of menopause. A previous study reported that both postmenopausal women and their healthcare providers believed that attitudes toward menopause can have an important role in the formation of women's experience about menopause 5 . The same finding was also reported by additional prospective studies 6 .…”
supporting
confidence: 64%
“…Tellingly, in key books focusing on women 3 and ageing within the media and cultural spheres, such as Dolan and Tincknell’s (2012) Aging Femininities and Douglas’s (2020) In Our Prime , the word ‘menopause’ is not included as an index entry and is barely mentioned. The existing scholarship on menopause in the media is limited and almost exclusively based on analyses of news and magazine representations in Australia (Shoebridge and Steed, 1998) and the United States (Cimons, 2008; Gannon and Ekstrom, 1993; Gannon and Stevens, 1998), 4 but not the United Kingdom. Moreover, to date, there has been no account of the media’s growing interest in menopause in the last decade or so.…”
Section: Menopause In the Mediamentioning
confidence: 99%
“…Dans la recherche comparative sur les paradigmes culturels réalisée par Gannon et Ekstrom (1993), où il s'agissait de classifier la ménopause en fonction de trois catégories larges (paradigmes médical, de transition et en fonction de l'âge), toutes les personnes du paradigme « médical » ont manifesté des attitudes plus négatives à l'égard de la ménopause que celles qui avaient choisi les deux autres contextes. Même constat dans la recherche effectuée par Lock (1994), où une comparaison entre les représentations de la ménopause au Japon et aux États-Unis illustre clairement que 117 plus l'image de la femme ménopausée est socialement valorisée, moins les femmes font état de symptômes physiques ou psychologiques.…”
Section: Les Recherches Sur Le Vécu De Ménopauseunclassified
“…Non seulement cette vision médicalisée de la ménopause aurait-elle des effets sociaux négatifs sur chacune des femmes en particulier, puisqu'elle autorise un contrôle toujours plus grand de la médecine sur leur expérience et leur corps, mais, de surcroît, elle aurait pour effet d'oblitérer la réalité empêchant que soit perçue, socialement, la variété des situations de ménopause (Notman,1990;Gannon et Ekstrom, 1993). Cependant, peu de travaux scientifiques, jusqu'à présent, avaient tenté de faire valoir la parole des femmes sur leur vécu de ménopause.…”
Section: Les Recherches Sur Le Vécu De Ménopauseunclassified